2019
DOI: 10.1038/s41588-018-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate genome-wide analyses of the well-being spectrum

Abstract: We introduce two novel methods for multivariate genome-wide association meta-analysis (GWAMA) of related traits that correct for sample overlap. A broad range of simulation scenarios supports the added value of our multivariate methods relative to univariate GWAMA. We applied the novel methods to life satisfaction, positive affect, neuroticism, and depressive symptoms, collectively referred to as the well-being spectrum (N obs = 2,370,390), and found 304 significant independent signals. Our multivariate approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
309
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 263 publications
(332 citation statements)
references
References 56 publications
(61 reference statements)
9
309
2
Order By: Relevance
“…Multi-trait analysis is different from cross phenotype or pleiotropy effect analysis [3], where the null hypothesis is at most one trait is associated with the SNP. Of note, the proposed adaptive test aMAT is a general framework and can be easily extended to incorporate other multi-trait methods such as MTAG [13], N-GWAMA [34], and HIPOn [35]. To be specific, we can treat any other powerful tests as an individual MTA test and then apply aMAT to combine its results to further improve the power.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-trait analysis is different from cross phenotype or pleiotropy effect analysis [3], where the null hypothesis is at most one trait is associated with the SNP. Of note, the proposed adaptive test aMAT is a general framework and can be easily extended to incorporate other multi-trait methods such as MTAG [13], N-GWAMA [34], and HIPOn [35]. To be specific, we can treat any other powerful tests as an individual MTA test and then apply aMAT to combine its results to further improve the power.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a heritability of roughly 50% [5, 23], genome-wide association studies (GWASs) on AGG have not identified genome-wide significant loci that replicated [1]. Childhood cohorts often have rich longitudinal data and assessments from multiple informants and we aimed to increase power to detect genomic loci via multivariate genome-wide association meta-analysis (GWAMA) across genetically correlated traits [24, 25]. In AGG, twin studies have reported moderate to high genetic correlations among instruments, raters, and age [26–29].…”
Section: Introductionmentioning
confidence: 99%
“…We show that ASPHD1 is co-expressed with genes involved in neurotransmission and synaptic vesicle location and function. In particular, CELF4 is involved in neurodevelopmental regulation [66] and is associated with educational attainment [67], neuroticism and mood related alterations [68][69][70]. Notably, the potential contribution of ASPHD1 to reproductive function via a putative role in synaptic vesicle integrity is consistent with the biological roles of some Mendelian GnRH deficiency disorder genes.…”
Section: Discussionmentioning
confidence: 61%